Genome evolution : gene and genome duplications and the origin of novel gene functions - Meyer, Axel (Kluwer Academic Publishers, 2003)
In the years since the publication of Susumu Ohno\'s 1970 landmark book Evolution by gene duplication tremendous advances have been made in molecular biology and especially in genomics. Studies of genome structure and function prerequisite to testing hypotheses of genome evolution were all but impossible until recent methodological advances. This book evaluates newly generated empirical evidence as it pertains to theories of genomic evolutionary patterns and processes. Tests of hypotheses using analyses of complete genomes, interpreted in a phylogenetic context, provide evidence regarding the relative importance of gene duplication. The alternative explanation is that the evolution of regulatory elements that control the expression of and interactions among genes has been a more important force in shaping evolutionary innovation. This collection of papers will be of interest to all academic and industry researchers working in the fields of molecular biology, biotechnology, genomics and genome centers.
Keywords: rostliny; biologie; Plants; genetika, lékařská genetika; botanika; Fishes; genom; Genome; ryby